Antifungal activity of native isolates of Trichoderma spp. against phytopathogens - Martínez-Sánchez, Carolina; Gutiérrez-Ibáñez, Ana Tarín; Saavedra-Guevara, Claudia; Martínez-Bernal, Luz Raquel; Ramírez-Dávila, Francisco; Salgado-Siclán, Martha Lidya (Revista Mexicana de Ciencias Agrícolas, 2026)
Diseases represent one of the primary causes of loss in agricultural production. Although chemicals are a common alternative for controlling them, they generate adverse effects on human health and the environment. Therefore, sustainable options are required, such as the use of soil microorganisms with biocontrol activity, such as Trichoderma, a fungus that has multiple mechanisms of action against phytopathogens, stimulates the soil microbiota, improves nutrient absorption, and activates plant defense mechanisms. This research aimed to evaluate the antagonism of eleven native Trichoderma species against Botrytis cinerea, Fusarium oxysporum, Rhizoctonia solani and Sclerotinia sclerotiorum using the percentage of radial growth inhibition, the percentage of growth area, the degree of antagonism, and the presence of mycoparasitism. Dual confrontation was performed under in vitro conditions in the phytopathology laboratory of the Faculty of Agricultural Sciences of the Autonomous University of the State of Mexico. The isolates Trichoderma atroviride TH3 and T. asperellum Th11 stood out for their inhibition capacity, reduction of pathogenic growth, high degree of antagonism, and mycoparasitism. The degree of antagonism was assessed with coverage of up to two-thirds of the growth area over the pathogen. Rhizoctonia solani showed the lowest percentage of growth area and was the main target of mycoparasitism. The results suggest that Trichoderma species have potential for use in sustainable agricultural practices.